Role of CA 125 in predicting pathological response and recurrence in advanced stage non mucinous epithelial ovarian cancer - Ch, Srivalli; V. P., Gangadharan; G., Anupama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ovarian cancer is the most common gynaecological malignancy. Neo adjuvant chemotherapy (NAC) followed by interval cytoreduction is proven to be non-inferior to primary debulking surgery in advanced stage epithelial ovarian cancers (EOC). The data about patterns of reduction of CA125, its cut off value to predict chemotherapy response and recurrence in patients who receive NAC is heterogeneous with varying cut offs. This study aims to evaluate the role of CA125 as a predictive marker of pathological response and recurrence in cases of advanced EOC and to determine cut off for the same. Methods: This is a prospective study conducted in department of medical oncology, from December 2019 to May 2021. Patients of advanced stage EOC who are on NAC with carboplatin and paclitaxel combination were included (n=33). CA125 values before treatment, after each cycle of chemotherapy, post-surgery, during the course of adjuvant chemotherapy and every 2 months post treatment were noted. As the patient undergoes interval cytoreduction, histopathology reports were followed for chemotherapy response score (CRS). Imaging was done to detect recurrence during follow up, if CA 125 value increases. Results: The level of CA125 after third cycle of NAC showed significant correlation with chemotherapy response score and DFS in all the patients who were operable at the end of NAC. Patients with normal CA125 value (i.e. <35 U/ml) post 3 cycles chemotherapy had increased chance of having CRS 3 and longer DFS in patients with high grade serous carcinoma. Decline in CA125 value to less than 10 IU/ml post interval cytoreduction also correlates with DFS. Conclusions: Our study shows that CA125 levels before cytoreductive surgery predicts CRS and DFS of women undergoing NAC for advanced stage EOC.